Challenges of school feeding in Ghana: Its effect on enrolment and attendance - Issah Iddrisu; Ibrahim Mohammed Gunu; Nurudeen Abdul-Rahaman (Social Sciences and Humanities Open, 2022)
The study seeks to access challenges of the school feeding programme and its effects on enrolment and attendance in the Northern Region of Ghana. The review of relevant literature in this study identified the challenges within the school feeding programme which included political interference, non-involvement of the Ghana Education Service and the teacher. This retarded the efforts of the school feeding programme to better enhance the chances of increasing enrolment and attendance. These challenges found little space in many of the studies in the area of school feeding research.To better examine the challenges, the study used the multi-stage cluster sampling technique in the selection of respondents. The study applied questionnaire in the data collection process. Results were aided with the use of correlation and regression in the analysis of the data. The study found that political involvement have a negative impact (−0.096) in the delivery of the programme but significant to the operations of the school feeding programme in view of its P. value (0.000). It is also confirmed that the Ghana Education Service (0.340) with a P. value (0.000) and the teacher (0.659) with a P. value (0.000) have a strong predictive capacity of increasing enrolment and attendance. When Ghana education service and the teacher is given full control of the operations of the programme, they will impact positively on programme operations and as well enhance enrolment and attendance.